Cloud computing adoption reference model - Wan Abdul Rahim Wan Mohd Isa; Ahmad Iqbal Hakim Suhaimi; Nurulhuda Noordin; Afdallyna Fathiyah Harun; Juhaida Ismail; Rosshidayu Awang Teh (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents a study to conceptualize a cloud computing adoption reference model. The case study on the cloud computing adoption was done in one local public university in Malaysia.  The case study was conducted to understand in-depth and real context phenomenon by investigating the influencing factors of cloud computing adoption. The main objective of this study is to design a cloud computing adoption reference model. This study applied Technology-Organizational-Environmental (TOE) Framework by Tornatzky & Fleischer and Diffusion of Innovation by Rogers as the theoretical background of the Cloud Computing Adoption Reference. Ten interviews were conducted with key informants. The theme pattern analysis of data were done by using qualitative computer programs, Atlas.ti. The findings are shown in summarize patterns that supports the conceptualization of cloud computing adoption reference model. Future work include the adaption of cloud computing adoption reference model specifically for the niche area of mobile computing.